Pengaruh Islamic Corporate Governance dan Islamic Social Reporting terhadap Kinerja Keuangan Bank Syariah di Indonesia - Ibnu Trilaksono; Agrianti Komalasari; Chara Pratami Tidespania Tubarad; Yuliansyah Yuliansyah (Penerbit Goodwood, 2021)
Purpose: This study examined the effect of Islamic Corporate Governance and Islamic Social Reporting on the Financial Performance of Islamic Banks in Indonesia at Sharia Commercial Bank Companies Listed on the Indonesia Stock Exchange. Research methodology: This study used multiple regression as the method to analyze the result of the research. By using 14 shariah banking data, this research will analyze the performance of the Indonesian general bank. Result: This study indicates that the variables that affect Islamic bank performance in this research are not implemented effectively. Limitations: The sample of this study was only 14 Islamic commercial banks and only used the Islamic banking sector in Indonesia, which is listed on the Indonesia stock exchange. Contribution: This research is helpful for further research. One of the guidelines in choosing which variabels to use and which one to use in the study should be understood in selecting Islamic financial performance.